Amphiphilic additives in silicone oil tamponade and emulsification: an eye‐on‐a‐chip study. Issue 2 (6th August 2019) - Lu, Yongjie; Chan, Yau Kei; Lau, Long Hei; Wong, David; Wong, Jasper Ka Wai; Shih, Kendrick Co; Lai, Shiu Ming; Shum, Ho Cheung
Abstract: Aims: Recently, chemically modified silicone oil has been demonstrated as a reservoir for sustained release of intraocular drugs, many of which might be amphiphilic in nature. In this work, we study the effect of amphiphilic additives in silicone oil on emulsification under eye‐like movements. Methods: Three silicone‐oil‐soluble surfactants, namely DC749, MQ1640 and FZ2233, were used as model amphiphilic additives. The change of viscosity was measured by a rheometer in the cone‐and‐plate geometry. The interfacial tension (IFT) between silicone oil and model aqueous phase was measured by pendant drop tensiometry. Emulsification of silicone oil was induced by simulated saccadic eye movements on a cell‐coated eye‐on‐a‐chip platform for 4 days. The number of emulsified silicone oil droplets observed in the aqueous phase was assessed daily by optical microscopy. Results: Significantly more emulsified droplets were formed in silicone oil with DC749 or MQ1640 ( P < 0.05). However, such increase was not directly related to the change in IFT nor viscosity. Moreover, water droplets were also found in the silicone oil, but not in the control silicone oil without additive. Conclusions: The amphiphilic substances in silicone oil promoted emulsification. Besides typical oil‐in‐water drops that normally affect the eye, water‐in‐oil drops were also formed. Before silicone oil could be considered as a vehicle for drug delivery, the nature of the drug and its possible effect on emulsification and therefore on the pharmacokinetics needs to be investigated. An additional concern is that water‐in‐oil droplets in the eye would affect the optical clarity of silicone oil and might cause visual symptoms.